1992
DOI: 10.1128/mcb.12.5.2154-2164.1992
|View full text |Cite
|
Sign up to set email alerts
|

SEN1, a Positive Effector of tRNA-Splicing Endonuclease in Saccharomyces cerevisiae

Abstract: The SEN1 gene, which is essential for growth in the yeast Saccharomyces cerevisiae, is required for endonucleolytic cleavage of introns from all 10 families of precursor tRNAs. A mutation in SEN1 conferring temperature-sensitive lethality also causes in vivo accumulation of pre-tRNAs and a deficiency of in vitro endonuclease activity. Biochemical evidence suggests that the gene product may be one of several components of a nuclear-localized splicing complex. We have cloned the SEN1 gene and characterized the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…We have isolated two enzymes from extracts of Schizosaccharomyces pombe that were purified on the basis of their ATPase activity that was stimulated by either poly(U) or M13 sscDNA. Peptide sequence analyses of the purified proteins confirmed that the enzymes were encoded by the S. pombe homologue of SEN1 (splicing endonuclease), originally reported to be involved in the tRNA splicing pathway in S. cereVisiae (17,18). The removal of introns from precursor tRNAs is mediated by three catalytic enzymes: a site-specific tetrameric endonuclease that catalyzes both 5′ and 3′ cleavages (18)(19)(20), a monomeric tRNA ligase (21,22), and an NAD-dependent phosphotransferase that removes a 2′phosphate from the splice junction to produce mature tRNA (23).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…We have isolated two enzymes from extracts of Schizosaccharomyces pombe that were purified on the basis of their ATPase activity that was stimulated by either poly(U) or M13 sscDNA. Peptide sequence analyses of the purified proteins confirmed that the enzymes were encoded by the S. pombe homologue of SEN1 (splicing endonuclease), originally reported to be involved in the tRNA splicing pathway in S. cereVisiae (17,18). The removal of introns from precursor tRNAs is mediated by three catalytic enzymes: a site-specific tetrameric endonuclease that catalyzes both 5′ and 3′ cleavages (18)(19)(20), a monomeric tRNA ligase (21,22), and an NAD-dependent phosphotransferase that removes a 2′phosphate from the splice junction to produce mature tRNA (23).…”
mentioning
confidence: 76%
“…Peptide sequence analyses of the purified proteins confirmed that the enzymes were encoded by the S. pombe homologue of SEN1 (splicing endonuclease), originally reported to be involved in the tRNA splicing pathway in S. cereVisiae (17,18). The removal of introns from precursor tRNAs is mediated by three catalytic enzymes: a site-specific tetrameric endonuclease that catalyzes both 5′ and 3′ cleavages (18)(19)(20), a monomeric tRNA ligase (21,22), and an NAD-dependent phosphotransferase that removes a 2′phosphate from the splice junction to produce mature tRNA (23). Whereas each of these proteins provides a unique enzymatic activity in the precursor-tRNA splicing pathway, the role played by ScSen1p is not clearly understood at present.…”
mentioning
confidence: 76%
“…Strong expression within the neuromuscular axis results from use of this promoter. Given that SETX protein is maintained at tightly controlled levels [ 6 , 13 ], total protein levels were not elevated for combined mouse Setx and human SETX. Specifically, Arg2136His mutant SETX was determined to represent ~ 71% of total SETX protein in transgenic line #1920 that was used in this study.…”
Section: Case Presentationmentioning
confidence: 99%
“…Translational fusions were made between the two elements and a NLS-lacZ fusion contained on pDU254 (Ursic et al, 1995). The NLS in this fusion is from yeast SEN1, which codes for a putative nuclear RNA helicase (DeMarini et al, 1992). Complementary oligonucleotides (LSO103-LSO106, Table 2) were synthesized containing the UPF3 NES-A and NES-B sequences.…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…7A). The two putative NES elements identified in Upf3p R. L. Shirley and others In order to test whether NES-A and NES-B can function independently as signals for nuclear export, the NES elements were fused to a reporter protein consisting of a NLS derived from the yeast Sen1p protein (DeMarini et al, 1992) and βgalactosidase (see Materials and Methods). The NLS in Sen1p causes the wild-type protein and reporter fusions containing the NLS to localize exclusively to the nucleus with no staining in the cytoplasm (Ursic et al, 1995).…”
Section: A Sequence Element In Upf3p Directs a Nuclear Reporter Prote...mentioning
confidence: 99%